2012
DOI: 10.1073/pnas.1212708110
|View full text |Cite
|
Sign up to set email alerts
|

Atomic model of the human cardiac muscle myosin filament

Abstract: Of all the myosin filaments in muscle, the most important in terms of human health, and so far the least studied, are those in the human heart. Here we report a 3D single-particle analysis of electron micrograph images of negatively stained myosin filaments isolated from human cardiac muscle in the normal (undiseased) relaxed state. The resulting 28-Å resolution 3D reconstruction shows axial and azimuthal (no radial) myosin head perturbations within the 429-Å axial repeat, with rotations between successive 132… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
247
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(272 citation statements)
references
References 45 publications
(45 reference statements)
22
247
1
2
Order By: Relevance
“…Structural evidence for interaction of S1 with the proximal S2 tail from the same molecule has been observed for isolated heavy meromyosin (HMM, a soluble fragment of myosin consisting of two S1 heads attached to S2) 3942 , myosin molecules 4043 , and intact thick filaments 13,7,8 . The first 3D structure of a folded state of myosin, named the interacting heads motif (IHM), came from a cryo-EM study of unphosphorylated smooth muscle myosin 39 and describes a 2.0-nm-resolution map of an asymmetric interaction between the S1 domains.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Structural evidence for interaction of S1 with the proximal S2 tail from the same molecule has been observed for isolated heavy meromyosin (HMM, a soluble fragment of myosin consisting of two S1 heads attached to S2) 3942 , myosin molecules 4043 , and intact thick filaments 13,7,8 . The first 3D structure of a folded state of myosin, named the interacting heads motif (IHM), came from a cryo-EM study of unphosphorylated smooth muscle myosin 39 and describes a 2.0-nm-resolution map of an asymmetric interaction between the S1 domains.…”
mentioning
confidence: 81%
“…The IHM has also been observed in other classes of muscle myosin, including striated muscle myosins 41 , and in images of intact thick filaments isolated from a variety of muscle types 16 . Thick-filament structures of 2.0- to 4.0-nm resolution have been obtained with cryo-EM for tarantula skeletal muscle 1,2 , Limulus telson muscle 3 , and vertebrate cardiac muscle 7,8 . The solved crystal structure of human β-cardiac proximal S2 reveals possible charge interactions between the S2 and the S1 (ref.…”
mentioning
confidence: 99%
“…The net effect of how coexisting wild-type and N2B-deficient titin isoforms will affect passive stiffness is difficult to predict, especially as data on the spatial organization of titin within the intact sarcomere structure is scarce. Based on three-dimensional single-particle analysis of electron-microscopy micrographs, Aband titin might exist in pairs (Al Khayat et al, 2013;Zoghbi et al, 2008). The distal tandem Ig segment has been suggested to form a higher-order structure of a side-to-side hexamer (Houmeida, et al, 2008).…”
Section: Modulation Of Force Development Kinetics By Titinmentioning
confidence: 99%
“…Furthermore, a recent X-ray diffraction study performed by Farman and co-workers showed that LDA might be based on the ordering of weakly bound cross-bridge orientation prior to activation (Farman et al, 2011). Titin winds along the myosin filament (Al Khayat et al, 2013), and it is tempting to speculate that increased passive tension affects myosin such that it enhances the probability of cross-bridge transitions to forcegenerating states, as reflected by the higher k ACT and k TR in myofibrils from knockout compared with wild-type mice in our study. Regarding the physiological situation when the sarcomeres are stretched during diastolic filling of the heart, the acceleration of cross-bridge cycling by increased titin-based passive tension might compensate for the potential slowing down of cross-bridge cycling resulting from the reduction of filament overlap.…”
Section: Modulation Of Force Development Kinetics By Titinmentioning
confidence: 99%
“…The S2 and light meromyosin (LMM) subfragments comprise a long tail that dimerizes to form a coiled coil. Polymerization of LMM produces a rod-like thick filament, with soluble S2 pointing radially outwards 142,143 . The S1 subfragment comprises the globular multi-domain head, which binds actin and hydrolyses ATP, and the neck region, which is stabilized by the myosin essential light chain (ELC) and the regulatory light chain (RLC) 144 .…”
Section: Hypotensionmentioning
confidence: 99%